Strategi Flipped Classroom Sebagai Upaya Meningkatkan Pemahaman Kandungan Al-Qur’an Dan Hadits - Fatima Z, Siti; Rahmat; Qutsiyah, Dewi Afiatul; Nasucha, Juli Amaliya; Manan, Mahmud (Chalim Journal of Teaching and Learning, 2022)
Research data is all information obtained to support the running of the research. The data in the study is divided into two forms, namely primary data (principal) and secondary data (supporting). The data source in the study is the subject from which the data was obtained. The primary data sources in qualitative research are words and actions, the rest are additional data such as documents and others. The results of this study found several aspects, namely consisting of; First, from the aspect of implementing flipped classroom mode learning, it is concluded into three groups; 1) Flipped Classroom learning planning, 2) Implementation of Blended Learning, and 3) Assessment. Second, from the aspect of Implications, several impacts were found on Flipped Classroom learning, including; 1) Learning motivation, 2) Independence, and 3) the Development of Qur'an and Hadith Learning. Then the Ketiga is an inhibitory aspect that includes 14 among others; 1) Assessment Online, 2) Evidence of Student Process, 3) Student Memory, 4) Parental Support, 5) Parents' Fair Play, 6) Parental Saturation, 7) Student Slowness, 8) Student Trust, 9) Shame, 10) Facilities and Infrastructure, 11) Teacher HR, 12) Parents' HR, 13) Parent Spirit, and 14) Student Spirit. The efforts to overcome the obstacles are parent counselling and exploring innovations and potential teachers' abilities for technology and information.